Education for parents to children's further education - Putri, Raudya Setya Wismoko; Prajanti, Sucihartiningsih Dian Wisika; Juhadi, Juhadi; Alimi, Muhammad Yasir (Universitas Negeri Yogyakarta, 2025)
The people of Ujungalang Village, Kampung Laut, Cilacap, still have some obstacles to implementing education. This can be seen from the many school-age children who have only finished elementary school and prefer to work and not continue their education to a higher level. This article aims to provide understanding and knowledge about education and change parents' mindsets regarding the importance of education for fishermen's children. The method used in this research is qualitative. The study was conducted in Ujunggalang Village, Kampunglaut, Cilacap. Research subjects included village heads, parents who work as fishermen, and children of fishermen. The results of this research include socialization activities and educational assistance through achievement motivation training (AMT) regarding the importance of education for fishermen's children to improve their standard of living. 1) Parents understand more about the importance of education and its impact on the continuity of life in the future for their children. 2) Parents are more aware of the critical role of education in children's development, especially regarding children's thinking patterns. 3) parents want to always encourage and be actively involved in their child's education.